Awareness of Education for Sustainable Development among Class IX Students of Yadadri Bhuvanagiri District in Telangana - Srinivas, Kadem; Srivastava, Rashmi (SCHOOL SCIENCE, 2017)
The purpose of the study was to find out the awareness of education for sustainable development among Class IX students of Yadadri Bhuvanagiri district in Telangana. The major objectives of the study were to study the awareness of sustainable development goals and utilisation of non-renewable resources with respect to sustainable development. The investigators adopted the descriptive survey method. The data were collected by using tools, viz., questionnaire (both open and closed-ended) and semi-structured interview. Purposive sampling (N=63) was used. The sample of the study was constituted of Class IX students of Gowtham Model School, Bhongir, District Yadadri Bhuvanagiri, Telangana, which is a private English medium school affiliated to the Directorate of School Education, Telangana. The two sections of Class IX students were selected as sample. The total sample (63) was: Section A consisting of 31 and Section B consisting of 32. The collected data were analysed by using both quantitative as well as qualitative techniques. The major findings showed that the students were not aware (61 per cent) of education for sustainable development. It was observed that students were much aware about utilisation of non-renewable resources. It was also observed that the syllabus needed to be incorporated more comprehensively on the topics of education for sustainable development and also students opined that activities should be organised in the school on education for sustainable development programmes at regular intervals. It may be noted that the recent national and international initiatives on education for sustainable development are taken keenly on inculcation of activities and placing curriculum in various levels of school education programmes.